Student Engagment in Project-Based Learning at SMAN 1 Tengaran - Shahada, Rukma Amala; Mardhiyyah, Khansa'atul; Puspita, Malika Dwi; Purnomo, Purnomo (Journal of English Language and Education, 2025)
Student engagement is vital for effective English as a Foreign Language (EFL) learning, encompassing behavioral, emotional, and cognitive dimensions. However, many Indonesian classrooms remain teacher-centered, limiting meaningful participation. This study explores how Project-Based Learning (PjBL) fosters multidimensional engagement among eleventh-grade students at SMAN 1 Tengaran. Using a qualitative case study design, data were collected through classroom observations, interviews, and reflective documents. Thematic analysis revealed that PjBL enhances behavioral engagement through collaboration and persistence, emotional engagement through enjoyment and confidence, and cognitive engagement through curiosity and reflection. These dimensions interact dynamically, transforming students into active, motivated, and self-regulated learners. The study highlights the potential of PjBL to create an engaging, student-centered EFL environment that encourages learners to act, feel, and think as real language users.